Increasing nitrogen accumulation and reducing nitrogen loss with N-efficient maize cultivars. (2nd July 2020) - Li, Qiang; Kong, Fanlei; Wu, Yawei; Feng, Dongju; Jichao, Yuan
ABSTRACT: Many nitrogen-efficient (N-efficient) maize cultivars have been bred to meet increased food demand and allay urgent environmental concerns, but the effects of these cultivars on increasing N accumulation and reducing N loss in the maize system have not been reported. A two-year field pot experiment was conducted in Southwest China to evaluate the advantages of an N-efficient maize cultivar on N accumulation and N loss in 2014 and 2015. The results showed that the N-efficient maize cultivar ZH 311 had higher N uptake and accumulation ability than the N-inefficient maize cultivar XY 508, especially in the middle and late growth stages. ZH 311 maintained higher residual soil inorganic N in the appropriate growth stage, promoting soil N supply capability and enhancing N uptake while decreasing residual soil inorganic N at harvest and reducing the risk of N leaching. Higher nitrogen accumulation and residual soil inorganic N contributed to lower apparent N loss and apparent N loss efficiency for the N-efficient cultivar than for the N-inefficient cultivar. Moreover, N loss during the maize growth season mainly occurred before silking, and the N-efficient maize cultivar could effectively reduce N loss before silking because of its earlier N uptake ability. Overall, the selection of N-efficient maize cultivars is not only an important measure to enhance N use efficiency but also an important means to reduce the loss of N and environmental pollution, especially at low and medium N levels.